The Relationship between Active Smokers Status and Spermatozoa Motility in Sekar Moewardi Fertility Clinic in Surakarta - Bima Kusuma Jati; Slamet Riyadi; Vitri Widyaningsih (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Bacground: Infertility problem occurs on 15% couples. Fifty percent (50%) of the problem is caused by male. Cigarette smoking can increase free radical and cause spermatozoa oxidative stress. The study aimed to investigate the relationship between active smokers and spermatozoa motility in Sekar Moewardi Fertility Clinic in Surakarta. Methods: The cross-sectional analytic study was performed on 72 men aged 20-45 years who had semen analysis in Sekar Moewardi Fertility Clinic in Surakarta during 2014. Active smoker history was obtained by self reported questionnaire, and spermatozoa motility was obtained by medical record of the semen examination from the laboratory. Subjects were divided into active smokers and nonsmokers. The data was analyzed with SPSS 20.0 for Windows using Chi Square method. Results: The total number of active smokers was 39 (28%) and nonsmoker was 44 (61%). Subjects with motile spermatozoa were 47 (65%) and nonmotil spermatozoa were 25 (35%). It was found that there was no significant relationship (p = 0.247; RR = 1.45) between active smoker status and spermatozoa motility in Sekar Moewardi Fertility Clinic in Surakarta. The study also showed that spermatozoa motility was related to neither BMI nor age in all subjects. Conclusion: There was no significant relationship between active smoker status and spermatozoa motility in Sekar Moewardi Fertility Clinic in Surakarta. Further studies are needed to confirm and determine other risk factors which can decrease sperm parameter. Keywords: cigarrete, smoker, motility, spermatozoa, semen